OXIDATIVE STRESS AND MORPHOLOGICAL CHANGES IN THE BRAIN ON A HIGH-FAT DIET - Feruza Kh. Inoyatova; Mashkhura I. Abdullayeva; Komila G. Mirakhmedova (Central Asian Journal of Medicine, 2025)
The study examined the morphological changes, intensity of lipid peroxidation, and the activity of antioxidant enzymes superoxide dismutase (SOD) and catalase in the brain during a high-fat diet. The high-fat diet caused perivascular and pericellular edema, a reduction in the neuronal density of the molecular and pyramidal layers, as well as a decrease in antioxidant enzyme activity and an increase in lipid peroxidation processes in the brain. The obtained results indicate a disruption of the structural-functional capabilities of the brain due to enhanced lipid peroxidation and decreased activity of antioxidant systems in fatty liver disease.